2020
DOI: 10.14569/ijacsa.2020.0111156
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Surface Water Quality on the Upper Watershed of Huallaga River, in Peru, using Grey Systems and Shannon Entropy

Abstract: The assessment of the quality of surface water is a complex issue that entails the comprehensive analysis of several parameters that are altered by natural or man-made causes. In this sense, the Grey Clustering method, which is based on Grey Systems theory, and Shannon Entropy, based on the artificial intelligence approach, provide an alternative to evaluate water quality in an integral way considering the uncertainty within the analysis. In the present study, the water quality on the upper watershed of Hualla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In this section, we will proceed to describe the center-point triangular whitenization weight functions (CTWF) method, which can be described as follows: First assume that there is a set of objects, a set of criteria and a set of grey classes, according to the sample value Then the CTWF method is appreciated in a flowchart in Fig. 1 and are developed with the following steps [12], [14]- [16].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this section, we will proceed to describe the center-point triangular whitenization weight functions (CTWF) method, which can be described as follows: First assume that there is a set of objects, a set of criteria and a set of grey classes, according to the sample value Then the CTWF method is appreciated in a flowchart in Fig. 1 and are developed with the following steps [12], [14]- [16].…”
Section: Methodsmentioning
confidence: 99%
“…www.ijacsa.thesai.org In relation to other studies, Chu & Tan [7] applied the Grey Clustering method to evaluate the surface sediment quality of the Jiangsu coastal ocean, and showed that more emphasis should be placed on the management of the surface tidal flat sediment environment, especially on the treatment of the pollution source to improve the sediment quality for the sustainable development of the coastal zone. In the water quality assessment conducted by Delgado et al, [12] in the Huallaga River basin, it was shown that of the 21 monitoring points analyzed all of these were found -according to the Pratti index -to be uncontaminated. A point to highlight from the previous study is that Shannon Entropy was used to determine the value of the weights, a feature that was not used in the study by Liping et al study [18] where the weights were determined using the arithmetic mean.…”
Section: A About the Case Studymentioning
confidence: 96%
See 3 more Smart Citations